Effects of hydrothermal treatment on the properties of nanoapatite crystals - Liang, Wei (Dove Medical Press, 2012)
We report the synthesis of nanoapatite crystals via a hydrothermal reaction of hydroxyapatite precipitates. The impact of the reaction conditions on the properties of the crystals obtained were evaluated. The hydrothermal reaction that takes place markedly affected the crystallinity, morphology, and size of the nanoapatite crystals formed. High crystallinity and large crystal size were obtained at higher hydrothermal temperatures and longer hydrothermal reaction times. The nanoapatite crystals were needle-like when prepared under ambient pressure conditions and rod-like when prepared under increased pressure. The crystals prepared at ambient pressure had a larger aspect ratio compared with those prepared under increased pressure. The aging time of the initial hydroxyapatite precipitate significantly affected growth of the nanoapatite crystals. With other hydrothermal reaction conditions being equal, the fresh hydroxyapatite precipitate produced notably larger crystals than the aged hydroxyapatite precipitate. The influence of apatite morphology on osteoblast viability was studied by MTT assay. The results indicate that the rod-like apatite showed a better biological response than needle-like apatite in promoting cell growth. Transmission electron microscopy showed that large quantities of needle apatite entered into cells and damaged their morphology.